A Spoof Surface Plasmon Transmission Line Loaded with Varactors and Short‐Circuit Stubs and Its Application in Wilkinson Power Dividers. Issue 6 (23rd April 2018) - Zhang, Xuanru; Tang, Wen Xuan; Zhang, Hao Chi; Xu, Jie; Bai, Guo Dong; Liu, Jun Feng; Cui, Tie Jun
Abstract: A tunable spoof surface plasmon transmission line (SSP‐TL) is proposed and investigated, which is periodically loaded with varactors and short‐circuit stubs. Compared with the common SSP‐TL with open‐circuit stubs, the proposed SSP‐TL exhibits better compactness and higher tunability. The dispersion and impedance features are analyzed using the T‐matrix method. The proposed SSP‐TL can also be biased in a conventional microstrip bias circuit, and seamlessly integrated into microstrip circuits. As applications, a frequency‐reconfigurable and compact Wilkinson power divider is designed and fabricated using the proposed SSP‐TL as the λ/4 impedance transformer around 1 GHz, which is validated by both numerical and experimental results. It is shown that 35% (or 20%) frequency tunability is achieved in simulated (or measured) results, reducing the footprint to 46% of the conventional microstrip one. Abstract : A tunable spoof surface plasmon transmission line (SSP‐TL) is proposed, which is periodically loaded with varactors and short‐circuit stubs. A frequency‐reconfigurable and compact Wilkinson power divider is designed and fabricated using the SSP‐TL as the λ/4 impedance transformer. It provides a versatile method to transform passive devices composed of microstrip lines into frequency‐reconfigurable and compact ones.